Clinical and Microbiological Characteristics of Pyogenic Spondylodiscitis: A Retrospective Study - Subedi, Nirajan; Dhakal, Gaurav Raj; Regmi, Rabindra; Shrestha, Niraj Man (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Pyogenic spondylodiscitis (PS) incidence is rising globally, but microbial profiles vary significantly by region. Local data is crucial for effective empirical therapy. This study aimed to analyze the clinical and microbiological characteristics of microbiologically confirmed PS cases at a tertiary hospital in Kathmandu, Nepal. Method: We retrospectively reviewed 19 patients with culture-positive PS treated at Manmohan Memorial Teaching Hospital from January 2017 to December 2024. Data on demographics, comorbidities, inflammatory markers (CRP/ESR), pathogen identity, treatment modality, and clinical outcome were collected. Statistical analysis was performed using SPSS. Result: The mean age was 58.8±15.4 years, and 78.9% were male. Neurological deficits were observed in 7 patients (36.8%). Lumbar/Dorso-lumbar spine involvement was most common (63.2%). Mean initial C-Reactive Protein (CRP) and Erythrocyte Sedimentation Rate (ESR) were 148.6±50.3 mg/L and 68.7±11.2 mm/h, respectively. The dominant pathogens were Staphylococcus aureus (47.4%) and Escherichia Coli (31.6%). Surgical intervention was required in 52.6% of patients. The overall clinical success rate was 94.7%. Conclusion: The high prevalence of Gram-negative organisms, particularly E. Coli and endemic pathogens like Salmonella typhi, mandates that local empirical antibiotic protocols in Nepal ensure adequate coverage for Gram-negative bacilli. Aggressive, pathogen-specific treatment leads to excellent outcomes in this population.